Micrografting of almond (Prunus dulcis Mill.) cultivars Ferragnes and Ferraduel - Yildirim, H.; Onay, A.; Suzerer, V.; Tilkat, E.; Ozden-Tokatli, Y.; Akdemir, H. (Elsevier, 2010)
The success of various in vitro micrografting techniques, establishment of the rootstock, size of the microscion, and the effects of culture medium on the grafted seedling development for almond cultivars Ferragnes and Ferraduel were studied. In vitro germinated wild almond seedlings developed from seeds were used as rootstocks. Shoot culture initiation was successfully achieved from the above almond cultivars by culturing mature shoot tips from forced nodal buds, about 3-5 mm. on 0.7 mg/L BA and 0.01 mg/L NAA containing a MS medium. The regenerated adventitious shoots from in vitro cultures were maintained and proliferated by sub-culturing on a fresh medium every three to 4 weeks. Regenerated shoot tips, which were micrografted onto in vitro seedlings, resulted in the restoration of shoot proliferation. The results indicated that the most successful method for the grafting of tested almond cultivars was slit micrografting. High levels of micrograft take were achieved with all ranges of scions (4-15 mm) obtained from the regenerated shoot tips. Slow growth and lack of axillary shoot development on the micrografts were noticeable when the micrografts were cultured on hormone-free germination medium. In vitro micrografted planners were successfully acclimatized and no problems were encountered with the establishment of micrografted plants in vivo. The developed technique has demonstrated a high potential for application in the micropropagation of almond cvs. Ferragnes and Ferraduel and thereby, represents a feasible method for the renewal of almond orchards in Turkey and elsewhere in the world. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved.
Keywords: Almond; Micrografting; Restoring; Rejuvenation; Rootstocks; Scions